Efficacy of Programs Designed to Reduce the Incidence of Premarital Sexual Behavior Among Adolescents: A Systematic Review - Desy Ayu Wardani; Siti Khuzaimah Ahmad Sharoni; Endang Triyanto (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
The incidence of premarital sexual behavior worldwide is increasing despite the fact that it is known that it may cause health and psychological problems. Hence, interventions are needed to reduce the incidence of premarital sexual behavior. The aim of this study was to provide an overview of the reported interventions used to reduce the incidence of premarital sexual behavior in adolescents and identify the implications for nursing practice. A systematic review was conducted using The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The Scopus, Science Direct, Web of Science, and ProQuest databases were searched using the keywords